Understanding ‘The Four Phase’ of Coal Industries and its Economic Policy Implication in Indonesia: A Systematic Literature Review (SLR) Approach - Natasha; Rezki, Jahen F. (JURNAL EKBIS, 2023)
This study seeks to provide a thorough examination of the four stages of coal mining and production. As we will see, there are four major phases in the coal industry across the world: phase-in, phase-out, exporter, and established user. This entanglement is critical for Indonesia's coal phase-out. In this regard, Indonesia, as the primary provider, should grasp the dynamics of coal industries in order to correctly leave coal. We employ a Systematic Literature Review (SLR) to examine the possibilities of nations forming coalitions in the coal industry. The probe is critical because coal companies are associated with high-power politics that necessitate long-term contracts. We discovered that the majority of coal-using countries have a sophisticated yet tough policy. The desire to quit coal in the near future appears to be an impediment. It resonates with classsical political economy studies that to exit coal needs a common consensus between each countries.